A invisibilidade dos sujeitos na educação básica: pressupostos para construção de uma escola para todos - Sartin, Mariusa Alves (2023)
In classrooms of regular Basic Education schools, it is not uncommon to observe that some students with disabilities are silenced, that is, they are not guaranteed the right to voice or are not heard about their difficulties and aspirations, because they do not fit into a hegemonic education system. In this sense, this research therefore has the following starting question: how can the school enhance the formation of critical, more humanized subjects, with attitudes aimed at changes in the ways of living and coexisting? The general objective being to plan pedagogical practices aimed at intellectual and cognitive school training, observing whether they contribute to the experience and coexistence of different subjects, with equity. The authors who underpinned this investigation were Mantoan (2015), Freire (1994, 1997, 2019), Hooks (2013), Rancière (2002) and Boaventura (2002), among others, with their contributions regarding the recognition and acceptance of the various subjects. This is an educational action-research, carried out within the scope of the Professional Master's Stricto Sensu Teaching in Basic Education of the Postgraduate Program in Teaching in Basic Education of the Center for Teaching and Applied Research to Education (CEPAE) of the Federal University of Goiás (UFG), with 6th grade students from a regular school and students of different ages from a special school and their respective parents and/or guardians. To carry out the research, interventions were carried out in the regular school with the 6th grade students and in the special school with the 6th grade students of the regular school and with the special school students. For data collection, questionnaires with closed and open questions were used. During the research intervention, a documentary video entitled “School for all” was developed with the investigated students, which constitutes the first Educational Product of this research, available on the Youtube channel with free access, also hosted in the CEPAE Library, in the EduCapes Portal, at the 1st Cine Goiany Short Film Festival, the second Educational Product, in the form of an experience report, received the title “Seeing and being seen: Scenes from an intervention proposal. As a research teacher, it was up to me to accompany the production of the documentary, which was planned, elaborated, presented and evaluated by the 6th grade students of the regular school participating in the research. The research results indicate that the proposals for collaborative and interactive interventions developed throughout the research contributed positively to the humanistic formation of the research participants, enhancing a harmonious school coexistence, based on ethics, equity and respect for singularities. On the other hand, based on the data, we consider the need for new proposals that include a humanist education, in particular, long-term projects.